Análise do uso de medicamentos para hepatite C - Rios, Marcos Cardoso (2017)
Introduction: The dynamics in the development and use of drugs, as an essential part of the care process for patients with hepatitis C, requires equal dynamics in the evaluation of their use, as a way to improve the offer of patient care. Objective: To evaluate the profile of use, effectiveness and safety of medications for the treatment of hepatitis C. Materials and Methods: The thesis was divided into four chapters that sought to respond to the specific objectives of the research. To do so: 1 - a transverse review of the medical records of all patients with hepatitis C who received antiviral therapy with interferon / peginterferon and ribavirin between 2002 and 2012; 2-. The charts of all patients with hepatitis C treated with boceprevir or telaprevir in combination with peginterferon and ribavirin between the years of 2013 and 2015 were analyzed; 3 - a systematic review was conducted to assess the incidence of adverse reactions associated with pharmacotherapies; 4- the perception of a group of patients treated or under treatment with one of the therapeutic regimens for hepatitis C on the impact of adverse reactions was analyzed. Results: In article 1, 298 treatments of hepatitis C with interferon / peginterferon were analyzed, and the sustained response ranged from 40.8% to 58.3% among untreated and previously treated patients with recurrent disease. Regarding article 2, 48 treatments were analyzed that associated the use of telaprevir or boceprevir with peginterferon and ribavirin, presenting sustained response rates ranging from 61.5% associated with telaprevir to 50% to boceprevir. Response rates decreased to 22.8% with telaprevir and 15.4% with boceprevir, when considering the intentions to be treated. In article 3, 13 studies were selected that included 8,221 patients and highlighted 4,801 reports of adverse reactions with 41 different manifestations. The selection ranking shows preferences for the use of direct-acting antivirals and lower recommendation of protease inhibitors. The analysis of patient perceptions (article 4) showed that negative experiences associated with pharmacotherapy are among the main barriers in treatment. Conclusions: The largest cohort of the analyzed universes indicates that the main pharmacotherapy for hepatitis C between the years 2002 and 2015 was the association with peginterferon and ribavirin, remaining as immunomodulants and virustatics used in association with protease inhibitors. The use of combinations with boceprevir or telaprevir has not been shown to be satisfactory and should be avoided. Classical therapy with peginterferon and ribavirin should be preferred over aggregative therapy with protease inhibitors, since the reactions are more insidious and difficult to treat. Directacting antivirals are safer, although the evidence is less robust. Adverse drug reactions affect the daily and the way patients relate to disease and treatment in the perception of a group of patients. Analyzes of the results contribute to the medico-social and economic basis of regulatory activities and other decisions in the field of medication policy and treatment of hepatitis C.